PM2.5 Exposure at a Busy Traffic Intersection in Varanasi, India - Behera S.K.; Mudgal A. (My University, 2025)
At urban traffic intersections, stopping, idling, and acceleration behavior of traffic results in increased pollution levels and makes them pollution hotspots. Among all the pollutants, particulate matter (PM) significantly accelerates human mortality and morbidity rates. This study was conducted to find the effect of peak and off-peak traffic on PM exposure concentrations at a traffic intersection. PM data was collected for a week during the day for 15 min every three hours intervals at one of the busiest traffic intersections in Varanasi. Meteorological parameters like atmospheric temperature (AT) and relative humidity (RH) were also logged along with PM measurements to establish a relationship between PM exposure and meteorological parameters. The study found higher exposure values during off-peak and lower during peak traffic hours. The lowest exposure (26 µg m−3) was found during the early morning. In contrast, higher exposure (41 µg m−3) was observed during midday and evening off-peak traffic hours. In addition, the commuters are exposed to a higher inhaled dosage of PM2.5 during off-peak traffic hours. PM2.5 emitted from vehicle’s tailpipes and resuspension of road dust stays in the air as aerosol and does not disperse instantaneously. Thus, the accumulation of PM during morning and afternoon peak traffic might result in higher concentrations during midday and evening off-peak traffic hours. It might be one of the reasons behind higher exposure in off-peak traffic hours and lower exposure in peak traffic hours. However, the lowest PM exposure during the early morning might be due to continuous off-peak hours at night. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.